2014
DOI: 10.1161/atvbaha.114.303573
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Reservoir Pressure Corresponds to Cyclic Changes in Aortic Volume

Abstract: C entral (aortic) blood pressure (BP) waveform indices independently predict cardiovascular events and all-cause mortality, 1 but the physiological mechanisms to explain the waveform morphology remain disputed. The well-established wave reflection theory ascribes transmission of discrete forward and backward (incident and reflected) waves as the principal contributory factor underlying the shape of the central BP waveform.2 However, while providing a plausible description of central BP morphology, recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Contrary to our hypothesis, wave separation analysis revealed that the reflected wave was not enhanced by the BFR during walking. In this regard, recent reports indicate that the reflected wave emanates around the proximal aorta (6) and that wave reflection from the periphery does not appear to influence the rise of aortic systolic BP during leg cycling exercise (6,20,21). Leg BFR-induced elevation of aortic systolic BP might be supported by these notions but not by the traditional wave theory.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Contrary to our hypothesis, wave separation analysis revealed that the reflected wave was not enhanced by the BFR during walking. In this regard, recent reports indicate that the reflected wave emanates around the proximal aorta (6) and that wave reflection from the periphery does not appear to influence the rise of aortic systolic BP during leg cycling exercise (6,20,21). Leg BFR-induced elevation of aortic systolic BP might be supported by these notions but not by the traditional wave theory.…”
Section: Discussionmentioning
confidence: 95%
“…However, the present findings are not consistent with this arterial wave reflection theory. The observed increases in central BP can be explained by changes in IWA and RWA acting through impeded outflow (impaired diastolic discharge) (6,20,21). Exercise-induced change in aortic PP was correlated with corresponding changes in IWA and RWA, and changes in IWA were entered into the multiple regressional model as a significant independent determinant of the exercise-induced change in aortic BP.…”
Section: Discussionmentioning
confidence: 99%
“…Although the wave reflection theory may provide a plausible description of CBP morphology, recent studies indicate that the influence of wave reflection on CBP may be less than initially assumed due to wave dispersion along the aorta and entrapment of reflected waves in the periphery. Accumulating evidence has shown that the reservoir function has a significant contribution to the augmentation of CBP [40]. The aortic reservoir represents the buffering role of the highly elastic proximal aorta, and the reservoir pressure is the minimum hydraulic force needed for the ventricle to generate the blood flow.…”
Section: Differences Between Central and Peripheral Bp Measurementmentioning
confidence: 99%
“…This leads to augmented BP and results in left ventricular hypertrophy due to the increased myocardial load. The reservoir pressure is highly correlated with changes in proximal aortic volume, and parameters from the reservoir wave can predict cardiovascular events and correlates with left ventricular mass [40,41,42]. The excess pressure integral is the difference between the measured BP waveform and reservoir pressure, and is a measure of the extra work needed by the left ventricle.…”
Section: Differences Between Central and Peripheral Bp Measurementmentioning
confidence: 99%
“…12,13 In the latter population there was an improvement of the c statistic with the inclusion of aortic excess pressure into predictor models for CV events already containing conventional Framingham risk factors (including brachial BP). 13 This novel marker, representing excess left ventricular (LV) work, has been validated in humans, 14 and can be produced from pressure waveforms (oscillometric cuff or tonometry) without using a generalised transfer function, and is a promising area for future study.…”
Section: Improved Prognostic Capacitymentioning
confidence: 99%